Difference Gel Electrophoresis (DIGE) Methods and Protocols - Cramer, Rainer; Westermeier, Reiner (Methods in Molecular Biology, Methods and Protocols, 2012)
Protein analysis is increasingly becoming a cornerstone in deciphering the molecular mechanisms of life. Proteomics, the large-scale and high-sensitivity analysis of proteins, is already pivotal to the new life sciences such as Systems Biology and Systems Medicine. Proteomics, however, relies heavily on the past and future advances of protein purification and analysis methods.  DIGE, being able to quantify proteins in their intact form, is one of a few methods that can facilitate this type of analysis and still provide the protein isoforms in an MS-compatible state for further identification and characterization with high analytical sensitivity. Differential Gel Electrophoresis: Methods and Protocols introduces the concept of DIGE and its advantages in quantitative protein analysis. It provides detailed protocols and important notes on the practical aspects of DIGE with both generic and specific applications in the various areas of Quantitative Proteomics.